Theology and form : contemporary Orthodox architecture in America - Denysenko, Nicholas E. (University of Notre Dame Press, 2017)
In Theology and Form: Contemporary Orthodox Architecture in America, Nicholas Denysenko profiles seven contemporary Eastern Orthodox communities in the United States and analyzes how their ecclesiastical identities are affected by their physical space and architecture.